REAL AND POTENTIAL SPATIAL COMPETITION ON THE FOOD RETAIL MARKET - Zobova L.L.; Torbenko A.M. (Техника и технология пищевых производств)
In the global market, food sales are connected with two opposing trends. On one hand, new markets are appearing and the number of suppliers is increasing as well as the range of goods. On the other hand, the growth in the number of producers means intensification of competition. Local food producers have to deal with the optimal location problem for their outlets, taking into account potential and existing competitors. The solution to the problem can be based on spatial competition theory conclusions particularly using some spatial competition models. The given methodology is chosen for the research purposes. The article gives some definitions of such concept as «economic space» and «spatial competition», which enables the analysis and helps find disadvantages of the existing spatial competition models. The agent's economic space is created for differentiation of interests and is a result of the competition. Spatial competition is an imperfect competition of producers (dealers) for the share of market space by means of price tools. Some regressions are built to look into relations between the number and density of firms and the number and density of population in the cities. The analysis is based on real data about shops' locations in Siberia Federal District. It is found that there is not any dependence between wages and the number and density of population in the cities. The built regressions show that additional centripetal forces exist in the cities. It means that simple theoretical models of spatial competition describe the reality inaccurately and it's more useful to apply more sophisticated models. So, the competition level depends on the agent's location. The competition is decreasing near administrative borders because the price is higher due to transport costs. However, diminishing of transport costs can lead to the concentration of production in large markets or near them.